Analysing costs for bio-based materials in agriculture : an application of activity based costing on crop coverage - Johansson, Emma (SLU/Dept. of Economics, 2018)
The transition to a sustainable economy is a major challenge of our time that concerns most sectors in our society. Environmental, economic and social aspects are all important dimensions of sustainability, and agriculture is one of the most essential industries for the transition. The implementation of a bio-economy, i.e. an economy based on bio-materials and products, is seen as a key strategy towards sustainability. In this thesis a bio-based method for crop coverage in was investigated. By analysing activities applying a process perspective, information about cost systems and the economics of using bio-materials in agriculture were revealed.